Estudo experimental de um sistema de condicionamento de ar com rotores dessecantes - Silva, Márcio Gomes da (2010)
This work is presented in an air conditioning system using evaporative cooling coupled with desiccant rotor, which presents itself as an alternative to refrigeration system for vapor compression. In this sense, was mounted on the Solar Energy Laboratory UFPB in Joao Pessoa, an industrial-scale prototype of a desiccant cooling system for air conditioning, using two rotors desiccants, two rotary heat exchangers, evaporative coolers three, two burners natural gas, a water pump high pressure and five centrifugal fans. The proposal is to analyze the behavior of the system on the climatic conditions of hot and humid climate and also compare the results with other experimental and numerical. The system can operate in three configurations for operation and you were obtained and recorded data as the prototype cooling capacity, COP and system psychrometric conditions of the air supplied equipment to the air conditioned environment. All work done in assembling the prototype and the field of technology applied to air conditioning with desiccant rotor under the conditions of hot and humid climate are presented and analyzed. The results show that, even when operating in adverse weather conditions, the system can achieve performance similar to the vast majority of cooling systems using desiccant rotor and the thermal comfort can be achieved under conditions of climate in the summer of Joao Pessoa.